REAKSI PASAR MODAL ATAS KEBIJAKAN KENAIKAN CUKAI DI INDONESIA - Erik Alexander Gani; Yulia Efni; Andewi Rokhmawati (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study aims to analyze the reaction of the capital market to the increase in cigarette excise in Indonesia. This study focuses on cigarette companies listed on the Indonesia Stock Exchange as an increase in excise tax has an impact on the cigarette industry. There are 4 companies that are included in the cigarette industry which are the samples of this study. This study uses an event study to examine the effect of Abnormal Return, Trading Volume Activity and Bid-Ask Spread before and after the increase in excise tax. The findings of this study are that there is no difference in abnormal returns both before and after the announcement of the policy on the increase in cigarette excise in 2020. Other findings indicate that there is no difference in trading volume activity both before and after the announcement of the policy for the increase in cigarette excise in 2020. Other findings indicate that there is no difference in bids. ask spread both before and after the announcement of the 2020 cigarette excise tax increase.